Consistency of Mycobacterium tuberculosis-Specific Interferon-Gamma Responses in HIV-1-Infected Women during Pregnancy and Postpartum - Sasi R. Jonnalagadda; Elizabeth Brown; Barbara Lohman-Payne; Dalton Wamalwa; Carey Farquhar; Kenneth Tapia; Lisa M. Cranmer; Grace C. John-Stewart (Hindawi Limited, 2012)
Background. We determined the consistency of positive interferon-gamma (IFN-γ) release assays (IGRAs) to detect latent TB infection (LTBI) over one-year postpartum in HIV-1-infected women. Methods. Women with positive IGRAs during pregnancy had four 3-monthly postpartum IGRAs. Postpartum change in magnitude of IFN-γ response was determined using linear mixed models. Results. Among 18 women with positive pregnancy IGRA, 15 (83%) had a subsequent positive IGRA; 9 (50%) were always positive, 3 (17%) were always negative, and 6 (33%) fluctuated between positive and negative IGRAs. Women with pregnancy IGRA IFN-γ >8 spot forming cells (SFCs)/well were more likely to have consistent postpartum IGRA response (odds ratio: 10.0; 95% confidence interval (CI): 0.9-117.0). Change in IFN-γ response over postpartum was 10.2 SFCs/well (95% CI: −1.5-21.8 SFCs/well). Conclusion. Pregnancy positive IGRAs were often maintained postpartum with increased consistency in women with higher baseline responses. There were modest increases in magnitude of IGRA responses postpartum.